2024
DOI: 10.1101/2024.03.21.586093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unbiased complexome profiling and global proteomics analysis reveals mitochondrial impairment and potential changes at the intercalated disk in presymptomatic R14Δ/+mice hearts

Brian Foo,
Hugo Amedei,
Surmeet Kaur
et al.

Abstract: Background: Phospholamban (PLN) is a sarco-endoplasmic reticulum (SER) membrane protein that regulates cardiac contraction/relaxation by reversibly inhibiting the SERCA2a Ca2+-reuptake pump. The R14Delta-PLN mutation causes severe cardiomyopathy that is resistant to conventional treatment. Protein complexes and higher-order supercomplexes such as intercalated disk components and Ca+2-cycling domains underlie many critical cardiac functions, a subset of which may be disrupted by R14Delta-PLN. Methods: We develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 153 publications
0
4
0
Order By: Relevance
“…the analysis of cardiomyocytes obtained from different cavities of an individual adult wild-type mouse heart in the C57BL6N genetic background. Previous work from both our lab (Foo et al, 2024) and other groups (Rosca et al, 2008; Gómez et al, 2009; Hou et al, 2019) has shown PCC and higher-order protein supercomplexes to play key roles in the heart, ranging from energy production (i.e. mitochondrial CI/III/IV supercomplexes) to Ca +2 -handling (Alsina et al 2019).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…the analysis of cardiomyocytes obtained from different cavities of an individual adult wild-type mouse heart in the C57BL6N genetic background. Previous work from both our lab (Foo et al, 2024) and other groups (Rosca et al, 2008; Gómez et al, 2009; Hou et al, 2019) has shown PCC and higher-order protein supercomplexes to play key roles in the heart, ranging from energy production (i.e. mitochondrial CI/III/IV supercomplexes) to Ca +2 -handling (Alsina et al 2019).…”
Section: Resultsmentioning
confidence: 97%
“…as employed by Schulte et al (Schulte et al, 2023)) combined with high fraction numbers, and (ii) publicly available PPC databases are largely derived from the analysis of human cancer research cell lines, while organ-specific proteomes from other species such as the mouse heart are strongly underrepresented e.g. CORUM 4.0 contains <1% of entries curated from tissue or cardiomyocyte samples (Foo et al, 2024).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations